KEADILAN DALAM HUKUM WARIS TINJAUAN MASLAHAH MURSALAH - Amaliyah, Ilmy; Assaad, Andi Sukmawati; Kamal, Helmi (IAIN Palopo, 2023)
This article aims to examine the fairness of inheritance law, reviewing maslahah mursalah. Through searching primary and secondary sources, this article finds that inheritance means the transfer of something from one person to another, better known as the transfer of various rights and obligations regarding the assets of someone who has died to another person who is still alive. Men and women have equally strong rights in obtaining inheritance from their parents and their siblings. Therefore the 2:1 division between men and women is fair both from the perspective of inheritance law itself and from the maslahah murlah. by considering Islamic law to avoid undesirable things (harm).